Effects of used engine oil on slump, compressive strength and oxygen permeability of normal and blended cement concrete - Nasir, Shafiq; Chin, Siew Choo; Mohd Hasnain, Isa (2018)
Used engine oil (UEO) is recognized as a hazardous waste produced during engine servicing. Its disposal in an environmentally friendly manner is a big challenge. This paper presents the experimental results of an investigation of the effects of UEO on slump and hardened concrete properties. Three concrete groups; 100% cement (OPC) concrete, concrete with 60% OPC + 40% fly ash and concrete with 80% OPC + 20% rice husk ash were prepared. Each of the groups composed of a control mix and a mix with 0.15% dosage of UEO (this dosage was selected from previous studies). Slump measurement of fresh concrete confirmed that a small dosage of UEO reasonably improves the slump of concrete. Lignosulfonate molecule (a common class of water reducing admixture) consists of aromatic rings containing one of the ionic groups viz., OH−, COO−, SO32−. The chemical composition of used engine oil showed the presence of 37% SO3 content that may be the reason for the plasticizing effect. Used engine oil caused variation in the compressive strength in the range of ±20% as compared to the control mix. The compressive strength at 28, 56, and 180 days of 100% OPC concrete with UEO reduced by about 17%. In general, a small dosage of used engine oil caused a substantial reduction in coefficient of oxygen permeability and porosity of all concrete mixes, which is an indicator of enhanced long-term durability.